Music and revolution : cultural change in socialist Cuba - Moore, Robin D., 1964- (Music of the African diaspora ;, 2006)
Provides an introduction to the most prominent artists and musical styles that have emerged in Cuba since 1959, and to the policies that have shaped artistic life. Tracing the development of dance styles, nueva trova, folkloric drumming, and other forms, this book describes how the arts have become a point of negotiation between individuals.